Leucocyte-derived extracellular trap formation significantly contributes to Haemonchus contortus larval entrapment. Issue 1 (December 2015) - Muñoz-Caro, Tamara; Rubio R, Mario; Silva, Liliana; Magdowski, Gerd; Gärtner, Ulrich; McNeilly, Tom; Taubert, Anja; Hermosilla, Carlos
Abstract Background Polymorphonuclear neutrophil (PMN) and eosinophil extracellular trap (ETs) formation has recently been described as an important host effector mechanism against invading pathogens. So far, scarce evidence on metazoan-triggered ET formation has been published. We here describe for the first timeHaemonchus contortus -triggered ETs being released by bovine PMN and ovine eosinophils in response to ensheathed and exsheathed third stage larvae (L3 ). Methods The visualization of ETs was achieved by SEM analysis. The identification of classical ETs components was performed via fluorescence microscopy analysis. The effect of larval exsheathment and parasite integrity on ET formation was evaluated via Pico Green®- fluorescence intensities. ETs formation under acidic conditions was assessed by using media of different pH ranges. Parasite entrapment was evaluated microscopically after co-culture of PMN and L3 . ET inhibition experiments were performed using inhibitors against NADPH oxidase, NE and MPO. Eosinophil-derived ETs were estimated via fluorescence microscopy analysis. Results L3 significantly induced PMN-mediated ETs and significant parasite entrapment through ETs structures was rapidly observed after 60 min of PMN and L3 co-culture. Co-localization studies of PMN-derived extracellular DNA with histones (H3), neutrophil elastase (NE) and myeloperoxidase (MPO) in parasite-entrapping structures confirmed the classical characteristics of ETs.Haemonchus contortus -triggered ETs were significantly diminished by NADPH oxidase-, NE- and MPO-inhibition. Interestingly, different forms of ETs, i.e. aggregated (agg ETs), spread (spr ETs) and diffused (diff ETs) ETs, were induced by L3 .Agg ETs andspr ETs firmly ensnared larvae in a time dependent manner. Significantly strongeragg ETs reactions were detected upon exposure of PMN to ensheathed larvae than to exsheathed ones. Low pH conditions as are present in the abomasum did not block ETosis and led to a moderate decrease of ETs. Eosinophil-ETs were identified extruding DNA via fluorescence staining. Conclusion We postulate that ETs may limit the establishment ofH. contortus within the definitive host by immobilizing the larvae and hampering them from migrating into the site of infection. Consequently, H. contortus -mediated ET formation might have an impact on the outcome of the disease. Finally, besides PMN-triggered ETs, we here present first indications of ETs being released by eosinophils uponH. contortus L3 exposure.